Pengaruh Penggunaan Ragi Instan dan Ragi Alami dari Jeruk (Citrus Sinensis) Terhadap Mutu dan Karakteristik Roti Manis - Farhani Farhani; Syafruddin Syafruddin; Pardi Pardi (Jurnal Riset, Inovasi, Teknologi & Terapan, 2025)
Natural yeast is a mixture of flour, water, and or other components fermented with a natural starter containing lactic acid bacteria (LAB) and yeast. The mixture is used as a baking agent in the production of sweet bread. The natural yeast in this study used fermented sweet orange soaking water as the yeast. Natural yeast can change the availability of fiber fraction, protein, and increase mineral content in flour. The purpose of this study was to determine the effect of adding instant yeast and natural yeast on the quality and characteristics of sweet bread. The experiment consisted of the independent variables of instant yeast and natural yeast with concentrations of 10%, 15%, 20% instant yeast and 10%, 15%, 20% natural yeast. The observation parameters used included microbial contamination, moisture content, ash, organoleptic. The results showed that the treatment of adding different proportions of instant yeast and natural yeast had a significant effect on moisture content with the lowest and highest ranges of 18.5-35% instant yeast and 21.5-37.5% natural yeast (wet basis), ash content in instant yeast with a range of 0.84-1.50%, and in natural yeast with a range of 0.93-1.50%. Then in microbial contamination with the two treatments there are the same results which meet the SNI.